Longitudinal gut microbiota dynamics in Antarctic research mission crews - Lee, Min-Jung; Lee, Seung-Hwan; Min, Huitae; Nam, Tae-Wook; Hong, Soon Gyu; Oh, Bumjo; Kim, Joo Hyeong; Kim, Yeon-Ran; Kim, Bong-Soo; Seok, Yeong-Jae (Frontiers in Microbiology, 2025)
IntroductionA prolonged stay at Antarctic research stations poses unique challenges due to extreme environmental conditions, restricted diets, and cold temperatures, all of which can influence the gut microbiota, an important factor in host health. However, our understanding of how the Antarctic environment affects the gut microbiota remains limited due to small cohort sizes and short study durations.MethodsWe analyzed 467 fecal samples collected longitudinally from 48 participants who stayed at Antarctic stations for up to 16 months.ResultsBefore departing to the Antarctic bases, male participants exhibited three distinct types of gut microbiota, which were differentially altered during and after the stay, depending on the pre-existing microbiota type. Prevotella-dominant microbiota was more susceptible to environmental changes, including the diet, compared with Bacteroides-dominant microbiota. Although the dominant genera in the gut microbiota were stable across all microbiota types, minor genera with high variability could mediate changes in the microbiota. Sharing diets and having frequent contact resulted in cohabitation effects among genetically unrelated participants in the extremely isolated Antarctic environment. Although taxonomic composition shifted in response to the Antarctic environment, predicted functions of the gut microbiota remained relatively stable.DiscussionThis study reveals that long-term residence in Antarctic research stations alters the gut microbiota in ways that depends on the intrinsic microbiota prior to the mission. These findings enhance our understanding of human gut microbiota adaptation under extreme and isolated environmental conditions.